Pathological study of elective nephrectomies for a two year period - Sreedhar, V. Vijay; Paul, M. Charan; Sirisha, O.; Shivaram, P.; Sudhir, N.; S, Chandrakumar (International Journal of Research in Medical Sciences, 2017)
Background: Nephrectomies whether partial, total or radical are common surgical procedures these days with trauma being the most common cause of an emergency nephrectomy. The indications of elective nephrectomies vary with different age groups- malignancies being common in the elderly age group and non-neoplastic indications of nephrectomy may present in any age group. The present study was undertaken in view of the increasing elective nephrectomies in our area thus analyzing the common causes requiring nephrectomy as a treatment. The present study also aimed at determining the age and sex distribution of various renal lesions requiring a nephrectomy. Methods: It was a prospective study for a period of 2 years - January 2013 to December 2014. A total of 45 nephrectomies were included in the study. Detailed clinical, biochemical and imaging findings were taken into consideration before analyzing each case. Results: There was a male predominance(64.4%) and 26.6% of the cases were in the age group of 40-50 years. 95.5% of the nephrectomies were performed for a non-neoplastic indication. Involvement of the right and left kidney was almost equal in the study. Chronic pyelonephritis was the most common histopathological diagnosis(68.8%). Conclusion: Inflammatory causes more commonly required a nephrectomy in the study population. Chronic calculous pyelonephritis was the most common underlying pathophysiology leading to a nonfunctioning kidney thus highlighting the early treatment of renal calculi.